Characteristics, retention and readmissions of opioid-dependent clients treated with oral naltrexone - Bartu, Anne; Freeman, N.; Gawthorne, G.; Allsop, Steve; Quigley, A. (Taylor and Francis Ltd, 2002)
The aims of this study were to examine the retention rates of opiod-dependent clients treate with oral naltrexone and identify factors that influence retention in treatement of 981 opioid-dependent clients at a public out-patient clinic in Perth, Western Australia. The average retention period for all clients was 9.0 weeks. The factors associated with longer retention were being employed and referral source. Clients who were employed stayed significantly longer in treatment than unemployed clients. Clients referred from a pricate clinic were retained in treatment significantly longer than those referred from other sources (X=10.3 vs. 5.9 weeks). While the majority (80.8%) had one admission to naltrexone treatment, 19.2% presented for readmission, some on three or more ocassions in the study period. The median period between the end of the first episode of treatment and commencement of the second was 15.6 weeks. The median period between the end of the second episode of treatment and commencement of the third was 11.4 weeks. Those employed had a higher probability of being retained longer in treatment than those who were unemployed in subsequent treatment episodes. Clinicians should respect that initial retention in naltrexone is likely to be relatively short, and that a substantial proportion of clients will represent for further treatment.